Palatability of selected alpine plant litters for the decomposer Lumbricus rubellus (Lumbricidae). - Alexander Rief; Brigitte A Knapp; Julia Seeber (PLoS ONE)
On alpine pastureland the decline in large-bodied earthworm numbers and biomass after abandonment of management might be the result of a shift from highly palatable grass litter to poorly digestible leaf litter of dwarf shrubs. To test this hypothesis, we analysed nitrogen, phosphorous and total phenolic contents of fresh and aged litter of eight commonly occuring alpine plant species and compared consumption rates of these food sources in a controlled feeding experiment with Lumbricus rubellus (Lumbricidae). Furthermore, we analysed the microbial community structure of aged litter materials to check for a relationship between the microbial characteristics of the different plant litter types and the food choice of earthworms. Plant litters differed significantly in their chemical composition, earthworms, however, showed no preference for any litter species, but generally rejected fresh litter material. Microbial community structures of the litter types were significantly different, but we could find no evidence for selective feeding of L. rubellus. We conclude that L. rubellus is a widespread, adaptable ubiquist, which is able to feed on a variety of food sources differing in quality and palatability, as long as they have been exposed to wheathering.